The effect of salinity and ascorbic acid on the germination of Fimbristylis miliacea - Lazarte, Menche P.; Fuentes, Rolly G. (2011)
Germination is a crucial period in the life cycle of plants. At this stage, plants are more susceptible to stressors such as salinity. Antioxidants such as ascorbic acid have been reported to lessen salinity stress by enhancing stress tolerance at germination level. In this study, the effect of salinity and ascorbic acid on the germination of F. miliacea was determined. Germination rates decreased as NaCl concentration as high as 200 mM and 250 mM. After pre-treatment of F. miliacea seeds with different concentrations of ascorbic acid, germination rates significantly increased. There was also significant differences in the lengths of the radicle and hypocotyl of the F. miliacea seedlings in the different ascorbic acid concentrations.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and Tecchnology